Peningkatan Kompetensi Guru PAUD: Implementasi Digital Pembelajaran Mendalam di PAUD - Andrisyah; Ifat Fatimah Zahro; Dedah Jumiatin; Rita Nurunnisa (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
The development of digital technology demands a transformation in early childhood education (PAUD) practices, including in the pedagogical aspects and teacher competencies. This community service activity aims to improve the competence of PAUD teachers in implementing digital-based deep learning. This program involves interactive training, mentoring, and introduction to educational digital media. The activity was carried out in collaboration with the PKG PAUD Cipanas District, Cianjur, which was attended by 40 early childhood teacher education, both formal and non-formal. The results of the activity showed an increase in teacher understanding and skills in designing and implementing deep learning strategies with digital support. The results of the satisfaction questionnaire showed that 92% of participants were very satisfied with this activity. Therefore, this training activity was able to contribute positively to improving the quality of learning at PAUD through the pedagogical integration of technology.